Uji Aktivitas Antibakteri Ekstrak Etanol Siput Gonggong (Strombus Turturella) Terhadap Bakteri Pseudomonas Aeroginosa dan Staphylococcus Aureus - Yunisa Friscia Yusri; Suhaera Suhaera; Suci Fitriani Sammulia; Doni Roga Septianus Siregar; Harlyanti Muthma’innah Mashar (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
The barking snail (Strombus turturella) is a type of sea slug that is found around the waters of Bintan Island, Riau Archipelago. Gonggong is a culinary object typical of Tanjung Pinang food, Gonggong also reflects the maritime area of ​​the Riau Archipelago Province which is geographically 95% of the sea area of ​​the gonggong snail containing secondary metabolites such as alkaloids, flavonoids and saponins. This study aims to determine whether the activity of the barking snail ethanol extract has activity as an antibacterial for Pseudomonas aeruginosa and Staphylococcus aureus. This study used 3 concentrations, namely 50%, 75%, and 100%, using a positive control of Amoxicillin and a negative control of DMSO. The results showed that the ethanol extract of the barking snail (Strombus Turturella) was able to inhibit the growth of Pseudomonas aeruginosa and Staphylococcus aureus at each concentration with the highest effective inhibition at 100% concentration, namely for Pseudomonas aeruginosa 16.5 mm which belongs to the group of strong inhibition , while for Staphylococcus aureus 10.26 mm it is included in the effective inhibition and is classified as moderate.